Sovereigns in the Marketplace: Consumer Groups and Citizenship (without Nations?) in the European Union - Covington, Elizabeth (Eurostudia)

(untitled) (Le Centre canadien d'études allemandes et européennes, 2006)
The enlargement of Europe and globalization are reconfiguring European consumerism. In this new context, personal, local and national agency in the social and the political relations of consumption are in great flux. I will use some recent language and circulars regarding GMOs to suggest that what consumers may be gaining in active agency through the creation of supranational agencies and NGOs and the proliferation of Internet activism, they may be losing in the accountability of their local governments. Further, the means by which “European” consumers are being created, possibly a classe objet in Bourdieu’s terms, reflects an erosion of national sovereignty and its crisis, producing what may be a “consolation narrative” to the spectre of the failure of democracy.